A macro-scale ruck and tuck mechanism for deformation in ion-irradiated polycrystalline graphite. (March 2021) - Liu, Dong; Cherns, David; Johns, Steve; Zhou, Yan; Liu, Junliang; Chen, Wei-Ying; Griffiths, Ian; Karthik, Chinnathambi; Li, Meimei; Kuball, Martin; Kane, Joshua; Windes, William
Abstract: A vein structure, which becomes more pronounced with increasing ion dose, was found on the surface of polycrystalline HOPG (highly oriented pyrolytic graphite) implanted by ex situ C + (up to 1.8 × 10 17 ions/cm 2 ), and in situ Ar + in a transmission electron microscope (TEM). These veins are found to be independent of the crystallographic orientations and are associated with the formation of pores. Underneath the veins, a triangular-shaped core was formed with the graphite platelet inside the core displaced up towards the surface. A macro-scale 'ruck&tuck' geometry was thus generated at these triangle structure boundaries. Progressive movement of dislocations along basal planes during irradiation was observed, and a mechanistic model was proposed on this basis to explain the vein formation. A small increase of c -spacing was observed with irradiation but it is believed that macro-scale vein formation plays a more vital role in the dimensional and property changes in polycrystalline graphite, especially when a stress gradient is present. The model proposed also explains the change of thermal expansion in HOPG with irradiation. Together with Heggie's 'ruck&tuck' and Barsoum's 'ripplocations' models, the present model is considered to have provided an additional experimentally proven mechanism responsible for irradiation behaviour in graphite materials. Graphical abstract: Image 1